Diabetes is a Risk Factor for Inflatable Penile Prosthesis Infection: Analysis of a Large Statewide Database. Issue 1 (21st January 2019) - Lipsky, Michael J.; Onyeji, Ifeanyi; Golan, Ron; Munarriz, Ricardo; Kashanian, James A.; Stember, Doron S.; Stahl, Peter J.
Abstract: Introduction: Although diabetes mellitus (DM) is often discussed as a risk factor for inflatable penile prosthesis (IPP) infection, the link between DM diagnosis and IPP infection remains controversial. High-quality population-based data linking DM to an increased risk of IPP infection have not been published. Aim: To evaluate the association of DM with IPP infection in a large public New York state database. Methods: The New York Statewide Planning and Research Cooperative System (SPARCS) database was queried for men who underwent initial IPP insertion from 1995–2014. Diabetic patients were identified using ICD-9-CM codes. Patients presenting for first operation with diagnosis or Current Procedural Terminology codes suggestive of prior IPP surgery were excluded. Chi-squared analyses were performed to compare infection rates in diabetics and non-diabetics within the pre- and postantibiotic impregnated eras. Multivariate Cox proportional hazards models were constructed to evaluate whether or not DM was independently associated with IPP infection in the time periods before (1995–2003) and after (2004–2014) the widespread availability of antibiotic impregnated penile prostheses. Main Outcome Measure: Time to prosthesis infection was measured. Results: 14, 969 patients underwent initial IPP insertion during the study period. The overall infection rate was 343/14, 969 (2.3%). Infections occurred at a median 3.9 months after implant (interquartile ratio: 1.0–25.0 months). Infectious complications were experienced by 3% (133/4, 478) of diabetic patients and 2% (210/10, 491) of non-diabetic patients ( P < .001). Diabetes was associated with a significantly increased IPP infection risk on multivariable analysis controlling for age, race, comorbidities, insurance status, annual surgeon volume, and era of implantation (Hazard Ratio: 1.32, 95% CI: 1.05–1.66, P = .016). Conclusion: Our analysis supports the notion that DM is a risk factor for IPP infection. This has important implications for patient selection and counseling, and raises the question of whether this increased risk can be mitigated by optimization of glycemic control before surgery.